High-protein oral nutritional supplement use in patients with cancer reduces complications and length of hospital stay: a systematic review and meta-analysis - Delsoglio, Marta; Capener, Rebecca; Smith, Trevor R.; Donald, Mhairi; Hubbard, Gary P.; Stratton, Rebecca J. (Frontiers in Nutrition, 2025)
IntroductionOral nutritional supplements (ONS) have been reported to improve nutritional status, quality of life and clinical outcomes in many patient groups. This systematic review investigated the effects of high-protein ONS (HPONS), ≥20% energy from protein, on clinical outcomes in cancer patients.MethodsA systematic review (searches to January 2025) identified 32 publications reporting results from 29 randomised controlled trials (RCTs) (n = 2,279) of HPONS (mean daily intake 580 kcal, 34 g protein, ranging from 5 to 365 days) alongside dietary intake in patients with gastrointestinal (GI) (14RCTs), lung (4RCTs), head and neck (4RCTs), liver (2RCTs), breast (1RCT), and mixed (4RCTs) cancers across hospital and community undergoing surgery, chemotherapy, and/or radiotherapy. Studies reporting relevant outcomes (complications, length of hospital stay (LOS), hospital readmissions, and mortality) were pooled into a meta-analysis (Comprehensive Meta-Analysis software v4).ResultsMeta-analysis showed a significant overall reduction (101 fewer per 1,000 patients) in complications (15RCTs, n = 1,230), including infectious, non-infectious and post-operative complications, and radiotherapy-related toxicities in patients using HPONS undergoing surgery and/or chemo/chemo-radiotherapy (OR: 0.62, 95% CI: 0.48-0.81; p = 0.0005; I2 = 0%) vs. control. The number needed to treat for preventing one additional complication with HPONS was 12 (95% CI: 9-29). A sub-group of studies (9RCTs) with HPONS enriched with omega-3 fatty acids also showed a positive effect on complications vs. control (OR: 0.69, 95% CI: 0.51-0.93; p = 0.02; I2 = 16%). A reduction in LOS was observed (8RCTs, n = 865) with HPONS (−0.26 days, 95% CI: −0.49 to −0.03; p = 0.02, I2 = 60%), while no significant difference was detected in hospital readmissions (5RCTs, n = 479) and mortality (7RCTs, n = 694).ConclusionThis systematic review and meta-analysis provide evidence that the use of HPONS (including those enriched with omega-3 fatty acids) alongside dietary intake is associated with a significant reduction in complications and LOS in cancer patients. The review found no significant effects on hospital readmissions or mortality. Given the heterogeneity of the patient population, further investigation is needed to comprehensively evaluate the effect of nutritional support on patient outcomes according to specific cancer and treatment types in various clinical settings.